Reliability Assessment of the Examination of the Sounds in the Temporo mandibular Joints in a Polish Patient Population - Osiewicz, Magdalena; Loster, Jolanta E; Wieczorek, A; Loster, Bartłomiej W (UI Scholars Hub, 2019)
Temporomandibular joints (TMJs) sounds are a common phenomenon in individuals with and without temporomandibular disorders (TMD). According to the Research Diagnostic Criteria of Temporomandibular Disorders (RDC/TMD), there are the following two distinguished types of sound: click and crepitation. The implementation of diagnostic criteria in studies should be accompanied by a reliability assessment of these criteria. Objective: This study aimed to assess the intra- and inter-observer reliability of joint sounds examination, using the officially translated and culturally adapted Polish version of the RDC/TMD. Methods: Ninety-eight (n = 98) consecutive adult patients were examined during two clinical sessions by two independent examiners, based on the RDC/TMD examination. Results: The intra-observer reliability of clicking and crepitation examination was generally excellent, with fair-to-good intraclass correlation coefficient in case of crepitation during lateral movement in the same direction as the crepitation. The inter-observer reliability of clicking and crepitation was excellent; however, it was fair-to-good for clicking and crepitation during lateral movement in the same direction as the click. Conclusion: The intra-observer and inter-observer reliability of the officially translated and culturally adapted Polish version of the RDC/TMD is similar to that of examinations conducted worldwide. Therefore, the use of this examination protocol is justified in Poland.